2012
DOI: 10.1682/jrrd.2012.01.0001
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic fitting, use, and satisfaction following lower-limb amputation: A prospective study

Abstract: Abstract-This study's objective was to determine how treatment-, environmental-, and facility-level characteristics contribute to postdischarge mortality prediction. The study included 4,153 Veterans who underwent lower-limb amputation in Department of Veterans Affairs facilities during fiscal years 2003 and 2004. Veterans were followed 1 yr postamputation. A Cox regression identified characteristics associated with mortality risk after hospital discharge following amputation. Older age, higher amputation leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
108
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 47 publications
2
108
2
12
Order By: Relevance
“…Data from several retrospective studies and several cohort studies in the United States [9][10][11][12][13][14] and abroad [15][16][17][18][19][20][21][22] show that the rates of prosthetic fitting vary by amputation level, with 1 yr prescription rates ranging from 49 to 93 percent for people with transtibial (TT) amputation, 14 to 57 percent for transfemoral (TF) amputation, 38 to 67 percent for knee disarticulation, and 38 to 100 percent for below-ankle amputation. However, these studies vary in their sampling frame and inclusion and exclusion criteria, and it is not possible to generalize findings to all persons who underwent major limb amputation in the United States or in the VA system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from several retrospective studies and several cohort studies in the United States [9][10][11][12][13][14] and abroad [15][16][17][18][19][20][21][22] show that the rates of prosthetic fitting vary by amputation level, with 1 yr prescription rates ranging from 49 to 93 percent for people with transtibial (TT) amputation, 14 to 57 percent for transfemoral (TF) amputation, 38 to 67 percent for knee disarticulation, and 38 to 100 percent for below-ankle amputation. However, these studies vary in their sampling frame and inclusion and exclusion criteria, and it is not possible to generalize findings to all persons who underwent major limb amputation in the United States or in the VA system.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies report rates of prosthetic prescription within the VA [8,[10][11][12]23]. Webster et al reported the highest rates of prosthetic prescription in any study for patients in a prospective cohort that included 87 persons from a single VA medical center with diabetes or peripheral vascular disease who were ambulatory prior to amputation (93% TT, 57% TF) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients are apprehensive about amputation because of the lack of proper rehabilitation facility and difficulty in accessing prosthesis, a fact confirmed in another study on amputation [10]. Where these facilities are available the psychological burden of being an amputee is minimized [6].…”
Section: Discussionmentioning
confidence: 96%
“…Patients therefore have other systemic conditions which require additional expensive investigations, resulting in extra economic burden on healthcare cost [6]. It is therefore evident that the socioeconomic impact of these amputations on the individual, their families and the health care system is enormous.…”
mentioning
confidence: 99%